Effect of resistance training on heart rate variability of anxious female college students - Li, Ran; Yan, Runsheng; Cheng, Weihao; Ren, Hong (Frontiers in Public Health, 2022)
Female college students are a group with high incidence of anxiety, and anxiety will lead to the disorder of autonomic nervous system (ANS), which will adversely affect their study and life. Resistance training plays a positive role in improving anxiety, but there is little evidence on whether resistance training can improve ANS of anxious female college students. Heart rate variability (HRV) has gained widespread acceptance in assessing ANS modulation. Therefore, the objective of this study aimed to investigate the effects of resistance training on heart rate variability (HRV) in anxious female college student. Method: A randomized controlled study of resistance training intervention was conducted in 27 anxious female college students that assigned randomly into an intervention group (𝑛 = 14) and a control group (𝑛 = 13); The intervention group was intervened by cluster training for 8 weeks. Self-rating anxiety scale (SAS) was used. ANS is evaluated by short-term HRV. Muscle strength was assessed by 1RM indirect method. Independent-sample 𝑡-test was used to test posttest-pretest scores between the intervention and control groups. Result: After the intervention, SAS score of the intervention group was significantly decreased (P<0.05), SDNN of the intervention group was significantly increased (P<0.05) and LF/HF was significantly decreased (P<0.05). Conclusion: The resistance training intervention adopted in this study significantly increased the HRV of anxious female college students and improved their autonomic nervous disorder.